ANALISIS FAKTOR YANG BERPENGARUH TERHADAP PERAN PETUGAS K3 DALAM MENDORONG PARTISIPASI PEKERJA KONTRAK UNTUK MEMBANTU PERENCANAAN MANAJEMEN RISIKO DI PEMBANGUNAN GEDUNG Y - Mohammad Afief; Baju Widjasena; Bina Kurniawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
To support the completeness of risk management required information from the parties that interact directly with potential dangers that exist in the work environment. Parties who interact directly with potential danger that contract workers so that the safety officer have important role in encouraging the participation of temporary workers in risk management. Implementation of risk management PT. X refers to OHSAS 18001. The results of the initial survey that there is still a minor accident that was not recorded or reported. This shows a lack of worker participation in risk management contracts. The research objective is to analyze the factors affecting the role of the safety officer in encouraging the participation of contract workers to help the planning of risk management. This research is a descriptive qualitative research with in-depth interviews and observation. Subjects were 1 and 5 main informant informant triangulation. The results showed the factors of knowledge and attitude of officers k3 regarding the parties should be involved in risk management as well as the phase of risk management is still not in accordance with OHSAS 18001, SMK3, and SKKNI. Factor methods used in encouraging the participation of contract workers, safety officer have never provides socialization and training materials about the importance of the participation of temporary workers to help the planning of hazard risk management in the workplace. Safety officer rarely discuss with contract workers to request information to workers on risk management. There has been no discussion of scheduling a regular basis to discuss risk management in each group of contract workers. More often used the lecture method when delivering socialization on safety talk, so communication which goes into one direction. There has been no documented work procedures requiring that the note of the information from the parties involved in the risk management process.